The Burden of Celebrity: the Impact of Ceo Certification Contests on Ceo Pay and Performance - Wade, James B.; Porac, Joseph F.; Pollock, Timothy G.; Graffin, Scott D. (Academy of Management Journal, 2006)
We used the results from Financial World's widely publicized certification contest, CEO of the Year, to investigate the impact of such contests on firm performance and executive compensation. A certification contest ranks actors on performance criteria that key stakeholders accept as credible and legitimate. We found that certified CEOs received higher compensation than noncertified CEOs when performance was high but lower remuneration when performance was poor. Although certifications generate positive abnormal returns when they are first announced, the longer-term impact of CEO certifications appears to be negative.